A Canadian Distinction of Note: London, Ontario’s Labatt Memorial Park, Baseball History’s Oldest, Continuously-Operating Baseball Precinct - Barney, Robert; Nowokowski, Riley (Ontario History, 2021)
It has been argued that London’s Tecumseh Park (renamed John Labatt Memorial Park in 1937) is the oldest, still functioning ball grounds in baseball’s lengthy history. This has been challenged persistently by scholars such as A.J. Bastarache on behalf of Clinton, Massachusetts, who argue that disastrous floods in London’s history “removed” the storied Tecumseh diamond from its original location to a completely new site, thus negating its record of continuous operation in one specific place. This paper examines newspaper and magazine articles related to the flood and the park to show that Tecumseh Park in 1883 and John Labatt Memorial Park in 1937 were renovated in timely fashion following floods and that the park did not change its physical location. Such findings provide further evidence undergirding the park’s bona fide heritage distinction as the oldest still operating ball ground in history.